Structural Elucidation of Bioactive Compound from the Fruit of Parkia timoriana - De, Biplab; Nath Choudhury, Swarnali; Paul, S.B. (Asian Journal of Chemistry, 2013)
The analgesic activity of the methanolic extract of fruit of Parkia timoriana (DC.) Merr. and its separated fractions were studied in acetic acid induced model. The in vivo antiinflammatory was also studied using carageenan induced rat paw edema method. The result of both studies indicated that the extract and its components possessed significant analgesic activity as well as antiinflammatory activity at the dose 100 mg/Kg bw. Both the activities were compared with standard drug aspirin for analgesic and diclofenan sodium for antiinflammatory. The structure of the bioactive compound has been characterized on the basis of spectral data such as IR, 1H NMR, 13C NMR and mass spectral studies.